Co-editor - Tsaousi, Christiana (My University, 2026)
Co-Editor of the Crossings Special Issue for Culture and Organization (Routledge/Taylor & Francis), an internationally recognised, peer-reviewed journal indexed in Scopus and the Social Sciences Citation Index (SSCI). The journal's current metrics are .5 (2024) Impact Factor, 1.8 (2024) 5 year IF, 2.4 (2024) CiteScore , Scopus), Q1 CiteScore Best Quartile . My role involves shaping the intellectual direction of the issue, overseeing the peer-review process, and ensuring the scholarly quality and thematic coherence of the special issue.